Effect of the upward curvature of toe springs on walking biomechanics in humans - Sichting, Freddy (Sci Rep, 2020)
Although most features of modern footwear have been intensively studied, there has been almost no research on the effects of toe springs. This nearly ubiquitous upward curvature of the sole at the front of the shoe elevates the toe box dorsally above the ground and thereby holds the toes in a constantly dorsiflexed position. While it is generally recognized that toe springs facilitate the forefoot’s ability to roll forward at the end of stance, toe springs may also have some effect on natural foot function. This study investigated the effects of toe springs on foot biomechanics in a controlled experiment in which participants walked in specially-designed sandals with varying curvature in the toe region to simulate toe springs ranging from 10 to 40 degrees of curvature. Using inverse dynamics techniques, we found that toe springs alter the joint moments and work at the toes such that greater degrees of toe spring curvature resulted in lower work requirements during walking. Our results help explain why toe springs have been a pervasive feature in shoes for centuries but also suggest that toe springs may contribute to weakening of the foot muscles and possibly to increased susceptibility to common pathological conditions such as plantar fasciitis.